1995
DOI: 10.1126/science.269.5225.841
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Tobacco Protoplasts Stimulated by Synthetic Lipo-Chitooligosaccharides

Abstract: fat Nodulation (Nod) factors are lipo-chitooligosaccharides (LCOs) secreted by rhizobia to trigger the early steps of nodule organogenesis in leguminous plants. A method to synthesize LCOs in vitro was developed. Synthetic LCOs alleviated the requirement for auxin and cytokinin to sustain growth of cultured tobacco protoplasts. LCOs containing C(18:1) trans-fatty acyl substituents were more effective than those containing cis-fatty acids in promoting cell division as well as in activating an auxin-responsive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…LCO signals (nodulation factors) secreted by nitrogen-fixing rhizobia were shown to play a key role in inducing nodule organogenesis in leguminous plants (1). Moreover, synthetic LCOs are efficient at femtomolar concentrations to alleviate the requirement of the phytohormones auxin and cytokinin to sustain growth of cultured protoplasts of the nonlegume tobacco (2). Within the tobacco cell, LCO and auxin signals are transduced via separate pathways that converge at, or before, the transcription of AXI1, a gene implicated in mitogen signaling.…”
mentioning
confidence: 99%
“…LCO signals (nodulation factors) secreted by nitrogen-fixing rhizobia were shown to play a key role in inducing nodule organogenesis in leguminous plants (1). Moreover, synthetic LCOs are efficient at femtomolar concentrations to alleviate the requirement of the phytohormones auxin and cytokinin to sustain growth of cultured protoplasts of the nonlegume tobacco (2). Within the tobacco cell, LCO and auxin signals are transduced via separate pathways that converge at, or before, the transcription of AXI1, a gene implicated in mitogen signaling.…”
mentioning
confidence: 99%
“…However, the kinetics were substantially different and lasted longer, indicating a different quality of the ionic perturbations, which may be crucial for the correct interpretation towards downstream activation processes. Since Nod factors and the structurally related chito-oligosaccharides have been shown to induce common responses in some test systems (Rö hrig et al, 1995;Savouré et al, 1997;Staehelin et al, 1994), the signalling pathways triggered by both compounds are likely to overlap partially. It remains to be shown by future experiments which elements of the signal transduction cascade are modulated in a specific way to allow the discrimination between elicitors of plant defence and symbiotic signals.…”
Section: Why Is There No Cytosolic Acidification?mentioning
confidence: 99%
“…In addition, plant hormones appear to play a role in Nod factor action since treatment with auxin transport inhibitors and secretion of trans-zeatin by bacteria can result in pseudo-nodule formation (Cooper and Long, 1994;Hirsch et al, 1989; for review see . Recently, RShrig et al (1995) found that synthetic lipochitooligosaccharides can replace plant hormones to stimulate cell divisions in tobacco protoplasts. In the absence of Rhizobium meliloti, alfalfa nodules can also be induced spontaneously under nitrogen-limiting growth conditions demonstrating that these plants have the capacity to induce the nodulation program (Truchet et al, 1989).…”
Section: Introductionmentioning
confidence: 99%